A Portable Diode Array Spectrophotometer. Issue 5 (May 2016) - Stephenson, David
A cheap portable visible light spectrometer is presented. The spectrometer uses readily sourced items and could be constructed by anyone with a knowledge of electronics. The spectrometer covers the wavelength range 450–725 nm with a resolution better than 5 nm. The spectrometer uses a diffraction grating to separate wavelengths, which are detected using a 128-element diode array, the output of which is analyzed using a microprocessor. The spectrum is displayed on a small liquid crystal display screen and can be saved to a micro SD card for later analysis. Battery life (2 × AAA) is estimated to be 200 hours. The overall dimensions of the unit are 120 × 65 × 60 mm, and it weighs about 200 g.